A Novel Therapeutic Approach for Colorectal Cancer Stem Cells: Blocking the PI3K/Akt Signaling Axis With Caffeic Acid - Park, Se-Ra; Kim, Soo-Rim; Hong, In-Sun; Lee, Hwa-Yong (Frontiers in Cell and Developmental Biology, 2020)
Cancer stem cells (CSCs) have been identified in a multiple of cancer types and resistant to traditional cancer therapies such as chemotherapeutic agents and radiotherapy, which may destroy bulk tumor cells but not all CSCs, contributing to reformation tumor masses and subsequent relapse. Moreover, it is very difficult to effectively identify and eliminate CSCs because they share some common phenotypic and functional characteristics of normal stem cells. Therefore, finding better therapeutic strategies to selectively target CSCs might be helpful to reduce subsequent malignancies. In the present study, we found that caffeic acid effectively suppresses self-renewal capacity, stem-like characteristics, and migratory capacity of CD44+ and CD133+ colorectal CSCs in vitro and in vivo. In addition, we also revealed that PI3K/Akt signaling may be linked to multiple colorectal CSC-associated characteristics, such as radio-resistance, stem-like property, and tumorigenic potential. To the best of our knowledge, this is the first study demonstrating that caffeic acid effectively targets colorectal CSC populations by inhibiting the growth and/or self-renewal capacity of colorectal CSCs through PI3K/Akt signaling in vitro and in vivo.